2016
DOI: 10.1177/1464420716640301
|View full text |Cite
|
Sign up to set email alerts
|

Vibro-acoustic behavior of functionally graded carbon nanotube reinforced polymer nanocomposite plates

Abstract: This paper presents the numerical investigation results carried out on vibro-acoustic behavior of functionally graded carbon nanotube reinforced polymer nanocomposite plate using combined finite element method and Rayleigh integral. Parameter studies are carried out to analyze the inFuence of nature of functional grading, loading of carbon nanotube, and structural boundary conditions on free and forced vibration and sound radiation characteristics in detail. It is found that natural frequencies are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…One of the limitations of this method is that it is valid only for simply supported boundary conditions; it cannot be generalised for all boundary conditions. George et al 20 analysed the vibration behaviour of carbon nanotube reinforced FG nanocomposite using finite element method (FEM) and Rayleigh integral technique. Using FEM, deflection at any point can be obtained, but one remains unaware of what is happening inside the element.…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations of this method is that it is valid only for simply supported boundary conditions; it cannot be generalised for all boundary conditions. George et al 20 analysed the vibration behaviour of carbon nanotube reinforced FG nanocomposite using finite element method (FEM) and Rayleigh integral technique. Using FEM, deflection at any point can be obtained, but one remains unaware of what is happening inside the element.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] From the studies, it is understood that the material properties of the CNT-reinforced polymer mainly depends on the structure of CNT, type of polymer, dispersion of CNT in matrix, fabrication process, and the method of analysis. [13][14][15][16] From the studies, it is understood that the material properties of the CNT-reinforced polymer mainly depends on the structure of CNT, type of polymer, dispersion of CNT in matrix, fabrication process, and the method of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many investigations are reported on the theoretical behavior of CNTRC flat/shell panel including the experimental validation. [13][14][15][16] From the studies, it is understood that the material properties of the CNT-reinforced polymer mainly depends on the structure of CNT, type of polymer, dispersion of CNT in matrix, fabrication process, and the method of analysis. Fidelus et al [17] reported the experimental data of the thermal and the mechanical properties of CNT/polymer composite using two types of polymer, as well as two CNT configurations based on the number of walls namely, singlewalled carbon nanotube (SWCNT) and multi-walled carbon nanotube (MWCNT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their extraordinary mechanical and thermal properties [1][2][3] as well as large aspect ratio and low density, 4,5 carbon nanotubes (CNTs) have been extensively used to reinforce polymer materials. [6][7][8] Previous studies have demonstrated that adding a small fraction of CNTs to a polymer matrix can significantly improve the effective properties of the resulting nanocomposite. [9][10][11] The interfacial bonding between a CNT and the surrounding polymer matrix significantly affects the performance of the nanocomposite.…”
Section: Introductionmentioning
confidence: 99%